Preventing Stunting Through ‘Pengenalan Tanaman Pangan Indonesia’ Media to Introduce Local Food - Widayanti, Melia Dwi; Adhe, Kartika Rinakit; Widayati, Sri; Maulidiyah, Eka Cahya; Malaikosa, Yes Matheos Lasarus; Safitri, Dhian Gowinda Luh (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
This study aimed to develop an AR book, PETANI (Introduction to Indonesian Food Plants), that can help teachers introduce local Indonesian food plants to prevent stunting. This research is a development project utilizing the ADDIE model, which comprises the Analyze, Design, Development, Implementation, and Evaluation stages. The subjects in this study included learning media experts, learning material experts, and 29 teachers from Banyuwangi Regency. The data collection technique used was a questionnaire administered during validation and user trials. The result of this research is that AR Book PETANI has been developed to the needs of children’s knowledge about local food plants. Additionally, AR Book PETANI is reported to be highly feasible, with an average score of 97.05%, making it suitable for implementation in learning about local food crops at PAUD institutions. This research concludes that the AR Book, with a theme of local food, has been developed as a medium to help teachers introduce local food and prevent stunting. The study’s results confirm the importance of utilizing augmented reality technology in learning media to support nutrition education and optimize the potential of local food as a strategy for preventing stunting from an early age.